Laboratornye markery adaptacii organizma biatlonistov vysokoj kvalifikacii k trenirovocnym nagruzkam - Rybina, I.; Shirkovets, E.; Nekhviadovich, A. (Science in Olympic Sport, 2017)
The article presents the results of multi-year biochemical monitoring of the training process of 32 highly qualified biathletes and the data of 6487 biochemical and hematological tests. Physiological values of biochemical markers were determined in highly qualified biathletes that allows to take into account the characteristics of the metabolism associated with athletes' gender, the stage of preparation, and the mode and direction of training loads. The use of the developed criteria for changes in biochemical indicators to assess the urgent and long-term adaptation makes it possible to evaluate the tolerance for physical loads, to avoid overstrain of the systems providing energy for muscular activity, and to develop optimal corrective actions at different stages of athlete`s preparation. Methodological approaches are described to evaluate the diagnostic informativeness of laboratory indicators for monitoring the training process.